Water Management and Sustainable Development in Alwar District: अलवर जिले में जल प्रबंधन एवं पोषणीय विकास - Yadav, Suman; Mishra, Purnima (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Water resources on Earth are fundamental for the development and survival of the entire biological world, including humans. Water plays a crucial role in the circulation and transmission of nutrients among various components of the ecosystem. The availability of water acts as a driving force for development, while its scarcity leads to destruction. It is well-known that water is a basic necessity for humans and a vital natural resource. Over the past few decades, humans have exploited this resource intensively through various activities. Consequently, several water-scarce regions, including parts of India and the world, have emerged as hotspots of water crises. Therefore, to address the water crisis, it is essential to conduct a thorough study of water resources and employ traditional as well as modern (non-traditional) water management methods. Only then will sustainable development be achievable. Abstract in Hindi Language: पृथ्वी पर जल संसाधन मानव सहित सम्पूर्ण जैविक जगत के विकास और उत्तर-जीविता के लिए आधारभूत संसाधन है। पारिस्थितिकी तंत्र के विभिन्न घटकों में पोषण तत्वों के गमनागमन एवं संचरण में जल महत्वपूर्ण भूमिका अदा करता है। जल की उपलब्धता विकास की प्रेरक है, जबकि जलाभाव में विनाश होने लगता है। सर्वविदित है कि जल मानव की बुनियादी आवश्यकता और एक प्रमुख प्राकृतिक संसाधन है जिसका विगत कुछ दशकों से मानव ने अपने विविध क्रियाकलापों के द्वारा तीव्र दोहन किया है परिणामस्वरूप भारत सहित विश्व के अनेक जलाभाव वाले क्षेत्र जल संकट के हॉट-स्पॉट्स के रूप में उभरकर सामने आये हैं। अतः जल संकट के निवारण हेतु जल संसाधन का समुचित अध्ययन कर परम्परागत व आधुनिक (गैर परम्परागत) जल प्रबंधन विधियों का उपयोग करना आवश्यक है तभी पोषणीय विकास सम्भव हो पायेगा। Keywords: उत्तरजीविता, आधारभूत संसाधन, परम्परागत विधियाँ, दोहन, पोषणीय विकास